The Definitive Guide to Grails - Rocher, Graeme (Springer, 2017)
The rise of Ruby on Rails has signified a huge shift in how we build web applications today; it is a fantastic framework with a growing community. There is, however, space for another such framework that integrates seamlessly with Java. Thousands of companies have invested in Java, and these same companies are losing out on the benefits of a Rails–like framework. Enter Grails.